In Spirit and in Truth Philosophical Reflections on Liturgy and Worship - Holtzen, Wm. Curtis; Hill, Matthew Nelson (Claremont Studies in Methodism and Wesleyanism, 2016)
An examination of liturgy and worship from a philosophical perspective